Mechanical wear prediction and prevention - Bayer, Raymond G. (Mechanical engineering (Marcel Dekker, Inc.), 1994)
This work details a practical methodology to determine the design parameters and materials necessary to obtain desired wear performances, stressing the idea of mechanical wear as a system property throughout. It offers a micrographic atlas of wear scar morphology for conducting failure analysis and equations for calculating contact stress and lubrication film thickness.